Competition, data and privacy in the digital economy towards a privacy dimension in competition policy? - Wasastjerna, Maria (International competition law series ;, 2020)
Increasingly, we conduct our lives online, and in doing so, we grant access to our personal information. The crucial feedstock of the world economy thus generated - the commercialization and exploitation of personal data and the intrusion of digital privacy it entails - has built an imposing edifice of market power. As we enter the third decade of the 21st century, this detailed exploration of the interlinkage between competition and data privacy takes a critical look at competition policy to evaluate whether the system in its current form and with the existing approach is capable of tackling the challenges raised by the role of personal data in the shift from an offline to an online economy.